تفويض السلطة مفتاح تحقيق التنمية الإدارية - سليمة, بوزيد (Sciences humaines, 2014)
تعالج المقالة الحالية عملية مهمة تتعلق بالتفويض والذي يعتبر إحدى المهارات التي غالبا ما يؤجل التعامل معها لفترات طويلة في حياة المديرين، نظرا لصعوبة القيام بها، والتفويض إحدى المهارات الإدارية التي يمكن تعلمها،وهي ذات أهمية كبيرة لتحقيق النجاح والتميز للقادة الإداريين. فإذا أراد القائد أن يكون لديه الوقت الكافي لإنجاز أعماله بشكل سليم، وأراد أيضا أن يحفز مرؤوسيه على القيام بأعمالهم ، فإنه يتعين عليه أن يعرف كيف يفوض المهام والمسؤوليات لموظفيه. فالتفويض هو أكثر الأدوات الإدارية، التي تعطي للقائد نتائج ايجابية ذات قيمة عالية للنجاح في عمله، ويمكن أن يحقق من خلالها ولاءا كبيرا من طرف مرؤوسيه ، ويمكن القول بأن التفويض يجب أن يسير بسرعة وبجودة  Abstract  :     Address the present article is an important process related to the mandate and which is a skill that often postpone dealing with it for long periods in the life of managers, given the difficulty to do, and mandate a management skills that can be learned, which is of great importance to achieve success and excellence of Management Leaders. If the commander wanted to have enough time to complete its work properly, and also wanted to motivate his subordinates to do their work, it must know how to delegate tasks and responsibilities to staff. Its mandate is more administrative tools, which give the commander of positive results, with a high value on success in his work, and can realize their loyalty after by his subordinates, and can say that the mandate should be running.